2001
DOI: 10.4049/jimmunol.167.2.910
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 2-Dependent Inhibition of Macrophage Class II MHC Expression and Antigen Processing by 19-kDa Lipoprotein ofMycobacterium tuberculosis

Abstract: Mycobacterium tuberculosis (MTB) induces vigorous immune responses, yet persists inside macrophages, evading host immunity. MTB bacilli or lysate was found to inhibit macrophage expression of class II MHC (MHC-II) molecules and MHC-II Ag processing. This report characterizes and identifies a specific component of MTB that mediates these inhibitory effects. The inhibitor was extracted from MTB lysate with Triton X-114, isolated by gel electroelution, and identified with Abs to be MTB 19-kDa lipoprotein. Electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
395
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 400 publications
(422 citation statements)
references
References 54 publications
(64 reference statements)
22
395
1
2
Order By: Relevance
“…In addition to the classical function of MHC-II molecules in presenting Ag to CD4 + T cells, MHC-II molecules can activate various cellular functions in immune or nonimmune cells when cross-linked by Ab or superantigen (75)(76)(77)(78). Previous studies showed that prolonged TLR2 signaling by mycobacterial lipoproteins, such as 19-kDa lipoprotein, inhibits MHC-II expression and Ag processing in macrophages (20,22). In our studies, prolonged TLR2 signaling by rMPT83 enhanced MHC-II expression and Ag presentation by macrophages.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the classical function of MHC-II molecules in presenting Ag to CD4 + T cells, MHC-II molecules can activate various cellular functions in immune or nonimmune cells when cross-linked by Ab or superantigen (75)(76)(77)(78). Previous studies showed that prolonged TLR2 signaling by mycobacterial lipoproteins, such as 19-kDa lipoprotein, inhibits MHC-II expression and Ag processing in macrophages (20,22). In our studies, prolonged TLR2 signaling by rMPT83 enhanced MHC-II expression and Ag presentation by macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The survival of M. tuberculosis may be associated with an inhibition of IFNg-dependent responses. Prolonged (.18 h) infection of macrophages with M. tuberculosis or exposure to lipoarabinomannan, 19-kDa lipoprotein, LprG, or LprA inhibits the IFN-g-induced expression of certain genes (20)(21)(22)(23)(24). M. tuberculosis also inhibits macrophage expression of CIITA and genes that are regulated by CIITA, including MHC-II, H2-M, and invariant chain (40).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…TLR2 contributes to innate resistance against M. tuberculosis (Reiling et al, 2002). In vitro investigations suggest that the triggering of TLR2 by M. tuberculosis may represent a double-edged sword: shortterm signalling through TLR2 activates macrophages and initiates inflammation via TNF-a secretion that may help to control the acute infection (Underhill et al, 1999); prolonged TLR2 signalling in macrophages results in downregulation of major histocompatibility complex (MHC)-II antigen processing, suppressing an acquired immune response (Gehring et al, 2004;Noss et al, 2001). The link between TLR2 triggering and phagosome maturation is controversial: Blander & Medzhitov (2004) reported that TLR stimulation promotes phagosome maturation, while provided evidence that TLR2 or TLR4 stimulation does not affect phagosome acidification or phago-lysosomal fusion.…”
Section: Introductionmentioning
confidence: 99%
“…LpqH is recognized by the immune system and induces T cell proliferation in vitro, stimulates DC maturation and autophagy and activates TLR-2 [67]. The protein alters the expression and presentation of antigens by MHCII [68]. 19kDa protein, induces macrophage apoptosis by caspase-dependent and -independent mechanisms with activation of the initiator caspase 8 and executioner caspase 3 [69].…”
Section: Lpqh (19 Kda Protein)mentioning
confidence: 99%